(untitled) (The Insight, 2024)
Introduction: Stomach cancer remains a major global health challenge, with significant morbidity and mortality rates. Accurate pre-operative assessments are crucial for effective surgical planning and improved patient outcomes. This study aimed to investigate the correlation between pre-operative investigative findings and per-operative observations in patients with stomach cancer. Methods & Materials: This retrospective cohort study analyzed 100 stomach cancer patients at Department of Surgery, Sylhet MAG Osmani Medical College Hospital, Sylhet, from September 2012 to August 2013. It included patients aged 18+ with confirmed diagnoses, focusing on demographic data, clinical presentation, and pre-operative imaging compared to intra-operative findings. Statistical analysis assessed correlation, sensitivity, specificity, PPV, NPV, and potential confounders using SPSS 26. Results: The study revealed that the majority of patients were aged 60 and above (50%), with a higher prevalence in males (60%). Abdominal pain (70%) and weight loss (50%) were the most common symptoms. Pre-operative imaging showed strong correlations with per-operative findings: tumor size (r=0.85, p<0.001), tumor location (r=0.78, p<0.001), depth of invasion (r=0.80, p<0.001), lymph node involvement (r=0.75, p<0.001), and distant metastasis (r=0.70, p<0.001). The sensitivity, specificity, PPV, and NPV of pre-operative findings were 85%, 80%, 83%, and 78%, respectively. Conclusion: The findings demonstrate that pre-operative imaging techniques are highly effective in predicting per-operative observations in stomach cancer patients. Comprehensive pre-operative evaluations using CT, MRI, and endoscopic ultrasound are essential for accurate surgical planning and improved patient outcomes. Integration of multiple diagnostic modalities can enhance the accuracy of pre-operative staging and contribute to better management strategies for stomach cancer.